2016
DOI: 10.1111/1365-2745.12674
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and spatial determinants of hybridization rate

Abstract: Summary1. Hybridization is a key evolutionary process with major consequences for conservation and speciation. However, sexual barriers interact with the local context to determine hybridization rates in a way that is still poorly explored. For instance, in the context of an expanding or introduced plant population, where a few individuals are isolated in populations dominated by heterospecific individuals, what is the hybridization potential? 2. To obtain baseline predictions on hybridization rate between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…One of the more perplexing aspects of the syngameon is how species retain their cohesiveness and distinctiveness despite occasional hybridization. To solve this paradox, it is important to recall that hybridization is both frequency‐ and density‐dependent: hybrids are produced in large numbers only episodically under conditions of extreme demographic imbalance among species, a process called Hubb's effect or the rare‐species effect (reviewed and modeled in Klein et al ., ). Such conditions are highly unstable.…”
Section: More Than the Sum Of Its Partsmentioning
confidence: 97%
“…One of the more perplexing aspects of the syngameon is how species retain their cohesiveness and distinctiveness despite occasional hybridization. To solve this paradox, it is important to recall that hybridization is both frequency‐ and density‐dependent: hybrids are produced in large numbers only episodically under conditions of extreme demographic imbalance among species, a process called Hubb's effect or the rare‐species effect (reviewed and modeled in Klein et al ., ). Such conditions are highly unstable.…”
Section: More Than the Sum Of Its Partsmentioning
confidence: 97%
“…Without reproductive isolation, coexistence of distinct species cannot be maintained because introgression can cause species to merge over time (Petit et al, 2004), eliminating their co-occurrence (Losos, 1990;Levin, 2006;Pollock et al, 2015), and potentially contributing to the observed patterns of overdispersion. In contrast, functional divergences between close relatives that allow them to occupy contrasting habitats likely limit gene flow between species (Klein et al, 2016), particularly if contrasting environments promote assortative mating, such as in sympatric live oaks in the southeastern USA, discussed in Section IV (Cavender-Bares & Pahlich, 2009). Empirical and theoretical evidence indicates that the likelihood of hybridization is impacted both by community structure and by demographic factors that influence pollen limitation (Klein et al, 2016).…”
Section: Introgression Incomplete Reproductive Isolation and Adaptamentioning
confidence: 99%
“…Theory predicts that, besides species intrinsic properties regarding pre-zygotic barriers and postzygotic isolation forces (see Vallejo-Marin & Hiscock, 2016, for a review), interspecies hybridization depends on environmental factors, more specifically the habitat and climate conditions, determining the relative abundance of species and the relative frequency of gametes involved in intra-and interspecific reproduction (Cannon & Lerdau, 2015;Klein et al,2017). In long-lived species predominantly consisting of large primarily outcrossing organisms with slow replacement rate (see above), under unfavourable environmental conditions, individual's survival is generally favoured over their reproductive investment (Bromham, 2011).…”
Section: Is Interspecies Hybridization Fre-quent and Widespread In Lomentioning
confidence: 99%